The effects of fertilizers and irrigation upon exchangeable cations in a light alluvial vineyard soil - Piaget, J. E. H. (Jean Edouard Henri) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 1953.